Use of TandemHeart as Bridge to Recovery for Antibody-Mediated Rejection in a Heart Transplant Patient - Rodriguez-Escudero, Juan P. (JACC Case Rep, 2020)
Antibody-mediated rejection is a major cause of graft failure, mortality, and morbidity among cardiac transplant recipients. We present the first reported case of TandemHeart (LivaNova, Pittsburgh, Pennsylvania) used in the management of antibody-mediated rejection associated with cardiogenic shock. (Level of Difficulty: Advanced.)